Trade Size and Components of the Bid-Ask Spread - Lin, Ji-Chai; Sanger, Gary C.; Booth, G. Geoffrey (Review of Financial Studies, 1995)
[The relation between theorized components of the bid-ask spread and trade size for a sample of NYSE firms is examined. We find that the adverse selection component increases uniformly with trade size. Conversely, order processing costs decrease with increases in trade size for all but the largest trades. We find that order persistence decreases with trade size. The adverse selection component is highest at the beginning of the day and lowest at the end of the day for all but the largest trades. Trades of NYSE firms executed on regional exchanges or NASDAQ contain a large order processing cost component but no significant adverse information effect.]